Rancang Bangun Wireless Nurse Call System berbasis Mikrokontroler sebagai Alat Bantu Orang Lanjut Usia untuk Memanggil Bantuan - Moch. Febryandana Nurfahri; Mochammad Hannats Hanafi Ichsan; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The number of elderly people in Indonesia was 29.3 million in 2021 and continues to increase annually. Elderly people are vulnerable to serious health problems that result in their inability to move independently and be left alone. This study developed a call system that can be easily operated by the elderly and connected to a caregiver's or family member's smartphone. The system consists of two devices, a client node that has a deep sleep mode and can be held by the elderly, and a control node that receives calls from client node. The control node displays a message on LCD, sounds the active buzzer, and sends a message to the Telegram application when the client node is active. The communication between the devices uses the Wi-Fi architecture provided by the Wi-Fi router and uses the simple and fast UDP protocol. System tests were performed to determine the processing time of the system and the power consumption of the client node. The test results showed an average client node processing delay of 6.8 seconds and a control node output delay of 3.6 seconds. The accuracy of the client node voltage reading is 99.36%, the average client node power consumption is 0.470 W when active and 0.076 mW when in deep sleep mode.